The Effect of Profitability and Managerial Ownership on Financial distress with Capital Structure as Moderating Variabel - TB Aria Maulana Ihsan; Irni Yunita (Akademi Akuntansi Indonesia, 2025)
The construction industry in Indonesia decreasing in profits in the 2019-2023 period, with several large companies recording consecutive losses. This study aims to analyze the effect of profitability and managerial ownership on financial distress and identify whether capital structure strengthens this effect of construction companies. Quantitative and moderated regression approach was used with secondary data financial statements of construction companies listed on Indonesia Stock Exchange (IDX) during 2019-2023. The results indicate profitability has a significant effect on financial distress. Conversely, managerial ownership not significant, but when combined with profitability, it can reduce the chance of financial distress. Capital structure not strengthen the profitability and financial distress, but reinforce the influence of managerial ownership. High managerial share ownership and balanced capital structure debt and equity, helps companies avoid financial distress. This study recommends that financial management in construction companies focus on enhancing profitability and managing capital structure to prevent financial distress.